STRATEGI PENINGKATAN PRODUKTIVITAS DAN KUALITAS KEDELAI LOKAL DENGAN PENDEKATAN PRODUKTIVITAS HIJAU (Jurnal Teknologi Industri Pertanian, 2019)
Increasing the competitiveness of soybean is an important thing and priority that must be done in order to fulfil the national food security. The objectives of the research  were (1)to map of local soybean problems associated with the concept of green productivity, (2) performance / green productivity index of soybean cultivation, and (3) design model of increasing soybean green productivity. The research was conducted in Banten Province on soybean production center. Data and information were collected through interviews and in-depth discussions on soybean business actors. The methods used were Green Value Mapping system, Green Produtivity Indeks, and Fuzzy Inference System (FIS). The results showed that the green productivity status of soybean agribusiness was in low category that need to be improved through innovation especially on seed supply, post harvest handling, and utilization of waste.Keywords : soybean, competitiveness, green productivity,  green value stream mapping, fuzzy inference system